Acute and chronic toxicity of glyphosate to native fish from San Luis province, Argentina - Jofré, Diego Martín (2015)
Public concern on the risks of glyphosate exposure has risen in Argentina, where glyphosate is used massively. Fish are widely used as models to assess the effects of contaminants. In this study we estimated the toxic effects of glyphosate (Roundup) on Cheirodon interruptus, Australoheros facetus and Jenynsia multidentata, three native fish species from San Luis, Argentina. Adult mortality was registered after acute exposure to Roundup (0 to 100 μL/L). The minimum concentration causing 100% mortality (MC100%M) and the maximum concentration with no mortality detected (MC0%M) were recorded. Biomarkers (hepatic enzymes and acetylcholinesterase) were assessed in fish that where chronically exposed to a sublethal concentration of Roundup. Inter-specific differences in sensitivity were not detected. The MC100%M was 50 μL/L and the MC0%M was 25 μL/L for the three species. Exposed fish had significantly higher hepatic enzymes and significantly reduced acetylcholinesterase activity levels compared to controls. This study provides valuable evidence on the impacts of glyphosate on native fish species.